Effect of Process Parameters and Double Gas Shielding on Mechanical and Metallurgical Behaviour during Gas Metal Arc Welding of Austenitic with Duplex Stainless Steel - Kumar, Ramesh (My University, 2014)
Austenitic and duplex stainless steel constitutes the largest stainless family in terms of alloy type and usage. One of the most important issues, in the case of dissimilar welds, is the evaluation of proper process parameters for welds between duplex and austenitic stainless steels. The aim of present study was to investigate the effects of process parameters i.e. current, voltage, filler wire, gas flow rate, type of gas and effect of double layer or single layer shielding on desired response in gas metal arc welding of dissimilar metal joining of stainless steels. The response measured were change in weld quality by tensile strength, impact strength, microhardness, weld distortion, visual inspection of cracks and metallurgical analysis of dissimilar metal joining of AISI 304 and AISI 316 with Duplex 2205. The effect of all the input parameters are analysed using the Taguchi experimental analysis. Tensile strength of the welded specimen were studied and found that current, voltage, filler wire and flow rate were significant parameters. Toughness of the weld specimen were studied and found that more toughness is achieved with increase in voltage and current. It was also seen that more toughness is achieved by using filler wire of Duplex 2205. For dissimilar metal joining of AISI 316 and Duplex 2205 maximum value of toughness (132.435 Joules) was obtained in the welded joint of parameters 160 A, 16 V, 14 L/min, filler wire of AISI 316, He and double layer shielding with flow rate of 8 L/min. For AISI 304 and Duplex 2205 maximum value of toughness (63.765 Joule) was observed under (trial 16). Microhardness test showed that for joining of dissimilar materials for AISI 304 and AISI 316 with DUPLEX 2205 the value of hardness was mainly dependent on welding current and shielding gas flow rate. Weld distortion of the weld specimen were studied and concluded that voltage, filler wire and interaction of current × voltage were the most dependent parameters leads to change in weld distortion. Weld distortion tends to decrease with decrease in current and voltage and by using filler wire of AISI 316. The surface morphology of the welded plates was characterized by scanning electron microscopy. The effect of heat input and flow rate of shielding gas on the microscopy is discussed. Dye penetrant test showed that welding was of very good quality and there was some defects shown when using pure Helium as a shielding gas. Joint quality result showed that for both the materials in welded region there were no major flaws and inclusion except a crack observed in a particular sample of dissimilar metal joining of AISI 304 and AISI 316 with Duplex 2205.
ME, MED
Keywords: Gas Metal Arc Welding; Metallurgical behavior; Mechanical Property; Double Gas Shielding; Austenitic Stainless Steel; Duplex Stainless Steel